1991
DOI: 10.3109/03009749109096808
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Substance P, Neurokinin A, Calcitonin Gene-related Peptide, Neuropeptide Y and Vasoactive Intestinal Polypeptide in Synovial Fluid from Knee Joints in Patients Suffering from Rheumatoid Arthritis

Abstract: We have studied the presence of five neuropeptides in knee joint synovial fluid from either patients suffering from rheumatoid arthritis and pain (n = 18) or being subjected to arthroscopy due to meniscal/cruciate ligament injuries (n = 13). Radioimmunoassay technique was used for peptide analysis using antisera SP2 against substance P (SP), K12 against neurokinin A (NKA), CGRPR8 against calcitonin gene-related peptide (CGRP), NPY1 against neuropeptide Y (NPY) and VIP2 against vasoactive intestinal polypeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 43 publications
1
53
0
2
Order By: Relevance
“…Neuropeptides have the potential to contribute to inflammatory disease as the "neurogenic component" via a variety of mechanisms (10). Levels of neuropeptides have been shown to be increased in samples of synovial fluid from patients with rheumatoid arthritis (11), and the ligation of sensory nerves in experimental joint inflammation is associated with a beneficial effect (12), providing evidence for involvement of sensory nerve activation in arthritis. Indeed, continued topical treatment with capsaicin has been shown to be beneficial in patients with hand osteoarthritis (13), and capsaicin creams are marketed for the alleviation of pain in diseases including both osteoarthritis and rheumatoid arthritis (14).…”
Section: 05) In Trpv1mentioning
confidence: 99%
“…Neuropeptides have the potential to contribute to inflammatory disease as the "neurogenic component" via a variety of mechanisms (10). Levels of neuropeptides have been shown to be increased in samples of synovial fluid from patients with rheumatoid arthritis (11), and the ligation of sensory nerves in experimental joint inflammation is associated with a beneficial effect (12), providing evidence for involvement of sensory nerve activation in arthritis. Indeed, continued topical treatment with capsaicin has been shown to be beneficial in patients with hand osteoarthritis (13), and capsaicin creams are marketed for the alleviation of pain in diseases including both osteoarthritis and rheumatoid arthritis (14).…”
Section: 05) In Trpv1mentioning
confidence: 99%
“…37 In patients with rheumatoid arthritis, and in rat adjuvent arthritis, increased expression of sensory neuropeptides has been reported in the synovial membrane and synovial fluid. [38][39][40][41] Sensory neuropeptides have also been implicated in vasodilatation. 42,43 In our study, CGRP-positive fibres were found mostly around the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expanding the CD4 ϩ CD25 AM is structurally related to CGRP and is an endogenous ligand of the calcitonin-related-like receptor (CRLR). 5 Although, increased CGRP levels have been found in patients and animals with arthritis, 25,26 and therefore, CGRP has been suspected as immunomodulatory factor, 27 CGRP does not efficiently down-regulate the synovial inflammatory response and fails to prevent CIA ( Figures 1C and 2D). 28 The difference in effectiveness between AM and CGRP could reside in the differential binding of both peptides to different binding complexes, which are formed by the CRLR and various receptor activity-modifying proteins (RAMP1, RAMP2, and RAMP3).…”
Section: Cd4mentioning
confidence: 99%